Status Ontologis Tuhan dalam Teologi Pembebasan Hassan Hanafi - Adi Candra Wirinata; Thoriq Ad Dakhil (UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract This article attempts to analyze Hassan Hanafi's theology of liberation. Belief in God has a great influence on human life. The direction of human life in the world is determined by his belief and understanding of God. In his theology of liberation, Hanafi positions God not as